Delayed Coronary Occlusion After Transcatheter Aortic Valve Implantation: Implications for New Transcatheter Heart Valve Design and Patient Management - Jabbour, Richard J (Interv Cardiol, 2018)
Transcatheter aortic valve implantation has revolutionised the treatment of patients with severe aortic stenosis and is the preferred treatment option for patients with elevated surgical risk. Outcomes have continually improved, but because of the nature of the procedure infrequent catastrophic complications, such as coronary obstruction, persist. Recently, data were published regarding delayed coronary obstruction (DCO), a phenomenon in which the obstruction occurs after the index procedure. DCO has important consequences for future research. In this article we will explore the implications for new transcatheter heart valve design and approaches to patient management to minimise the risk of DCO occurring.